New reactive rigid-rod aminated aromatic polyamide for the simultaneous strengthening and toughening of epoxy resin and carbon fiber/epoxy composites. (15th September 2020) - Wang, Weitao; Zhou, Guodong; Yu, Boshi; Peng, Mao
Abstract: In recent years, nanomaterial reinforced composites have been extensively studied, however, research on molecular composites, i.e. composites reinforced by rigid-rod macromolecules of large aspect ratio and superior mechanical properties, is still rare. In this study, we report that when a new organosoluble rigid-rod aromatic polyamide, poly(p-aminophenylene terephthalamide) (NH2 -PPTA), is used as a reinforcing agent of epoxy resin, it is dispersed in epoxy at molecular level at low contents but forms nanorod- or nanofiber-like aggregates in the matrices at higher contents, thereby transforming the molecular composite into a nanocomposite. The reactive amino side groups can not only improve the solubility of NH2 -PPTA in epoxy but also participate in the curing reaction, which leads to the formation of covalent bonds between NH2 -PPTA and the matrix. At a content as low as 0.7 wt%, NH2 -PPTA remarkably improves the strength and toughness of epoxy resin with a tensile strength of 100.7 ± 5.3 MPa and tensile toughness of 2860 ± 316 kJ/m 3, which are increased by ~74% and ~118%, respectively. The strengthening and toughening effects are comparable to those provided by graphene oxide, and are higher than by many other previously reported inorganic nanofillers. Moreover, NH2 -PPTA also significantly improves the mechanical properties of carbon fiber (CF)/epoxy composites. Flexural strength, total fracture energy and interlayer shear strength are increased by ~9%, ~67% and~27%, respectively. This is the first report on the transition of molecular composite to nanocomposite and the effective strengthening and toughening of epoxy resin and CF reinforced composites by NH2 -PPTA.